2008
DOI: 10.1007/s11250-008-9179-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different beak trimming age on performance, H-L ratio and antibody production to SRBC in laying hens

Abstract: The objectives of this study were to examine the effects of beak trimming age on performance criteria, H-L ratio, antibody production, the percentage of spleen and liver and external appearance. The chicks (Barred Rock) were randomly divided into 4 beak-trimming groups (non-trimmed (control), a trim at 1 d (1D), at 10 d (10D) and at 10 wk (10W)), each of 132 chicks. There were 6 replicate cages at beak trimming groups at rearing period. At 18 wk of age a total of 144 pullets were transferred to the layer house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
2
8
2
Order By: Relevance
“…The effects of beak trimming on egg production have often been the subject of investigations by researchers. While some (Guesdon et al, 2006;and Onbaşılar et al, 2009) have found increased rates of egg production as a benefit of trimming, others have reported nonsignificant effects (Carey and Lassiter, 1995;Gentle et al, 1997). Feed intake and feed conversion ratios were lower in small hens group (420 cm2/hen) than larger hen group (Table 2) Generally, the present result was agreement with Davis et al (2004) showed that feed consumption was lower in group of 361 cm2/hen than that of 484 cm2/hen.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The effects of beak trimming on egg production have often been the subject of investigations by researchers. While some (Guesdon et al, 2006;and Onbaşılar et al, 2009) have found increased rates of egg production as a benefit of trimming, others have reported nonsignificant effects (Carey and Lassiter, 1995;Gentle et al, 1997). Feed intake and feed conversion ratios were lower in small hens group (420 cm2/hen) than larger hen group (Table 2) Generally, the present result was agreement with Davis et al (2004) showed that feed consumption was lower in group of 361 cm2/hen than that of 484 cm2/hen.…”
Section: Discussionsupporting
confidence: 82%
“…This may be due to the lower egg production of this group. Some researchers (Davami et al, 1987;and Onbaşılar et al, 2009) reported the similar results. However other researchers (Cunningham and Ostrander, 1982;Quart and Adams, 1982;and Onbaşılar and Aksoy, 2005) reported contrary results.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Ab-AIV, AI-NDV, and SRBC antibody levels in the serum samples were measured with hemagglutination inhibition tests according to previous studies [22][23][24][25] and were expressed as the log 2 value of the corresponding dilutions. H/L was measured by using blood smears made with fresh blood [24]. Briefly, after staining with Wright's Giemsa solution, the heterophils and lymphocytes on the blood smears were counted under a light microscope.…”
Section: Population and Phenotypesmentioning
confidence: 99%